Effect of vitamin K2 in the treatment of nocturnal leg cramps in the older population: Study protocol of a randomized, double-blind, controlled trial - Li, Ying; Zhu, Rui; Wang, Li; Tan, Jing (Frontiers in Nutrition, 2023)
Introduction Nocturnal leg cramps (NLCs) are sudden contractions of the leg muscles, usually in the posterior calf muscles at night, affecting sleep quality. Because the precise pathophysiology of NCLs is unclear, different interventions have been proposed. There is conflicting evidence regarding the efficacy of conventional interventions in preventing cramps. Thus, the present study aims to investigate the effects of vitamin K2 for NLCs in a prospective randomized, double-blind, controlled trial. Methods and analysis This multicenter, randomized, double-blind, placebo-controlled clinical study will enroll older age (≥65-year-old) with two or more documented episodes of NLCs during 2 weeks of screening). Participants will be randomized to receive vitamin K2 or a similar-looking placebo for 8 weeks in a 1:1 ratio. Follow-up visits will be scheduled each week at the beginning of the 4-week intervention, then participants will be visited semimonthly. The primary outcome is the difference in the mean number of NLCs per week in the vitamin K2 and placebo arms. The secondary outcomes include the severity and duration of NLCs in the vitamin K2 and placebo arms. 200 patients will be needed, for this two-treatment parallel design study, to achieve a probability is 90 percent that the study will detect a treatment difference at a two-sided 0.04 significance level if the difference between treatments is 3.6 (difference in means between treatment arms) NLC events. Discussion Nocturnal Leg Cramps (NLCs) is a common musculoskeletal disorder in the general population, but effective and safe interventions have not been established. Our previous study has shown vitamin K2 was effective to reduce the frequency, severity, and duration of dialysis-related muscle cramps with a good safety profile. This randomized controlled trial (RCT) of rigorous methodological design will help to establish the effectiveness of vitamin K2 for the management of NLCs in older population. The findings of this RCT will encourage the studies of vitamin K2 in musculoskeletal disorders.